(untitled) (Conferencea, 2023)
Biopharmaceutical manufacturing, because of its complex nonlinear nature, is fraught with a myriad of process variations that can impact safety and efficacy of the drug. Since the introduction of concepts such as process characterization and design of experiments (DoE) over two decades ago, the biopharmaceutical industry has created and demonstrated considerable expertise in unravelling how the process affects the product. However, the role of raw materials (RM) has been somewhat overlooked and as a result has become the primary source of variability in process performance and product quality. The growing significance of the role of raw materials in the process control strategy is evident from the ICH Q8 guideline, which suggests that in the Quality by Design (QbD) framework the manufacturer must understand all sources of variability including the raw materials.